SMEs - THE MAIN PILLAR OF ANY ECONOMY - UNGUREANU, Anca (Annals of Spiru Haret University. Economic Series, 2020)
Abstract Micro and small and medium-sized enterprises (SMEs) account for 99% of EU businesses. They provide two-thirds of private sector jobs and contribute more than half of the total added value created by EU businesses. SMEs play an important role for economic and European growth, producing 60 of the European GDP. Also, SMEs play a major role in the innovation process and thus constitute an important element for a knowledge-based economy. At European and national level, various action programs have been adopted to support SMEs, with the aim of increasing the competitiveness of SMEs through research and innovation and improving their access to finance.